Ekspresi Lanskap-Agrikultur dan Pola Permukiman Masyarakat Peladang di Madura Timur - F, Redi Sigit.; Wulandari, Lisa Dwi; Santosa, Herry (RUAS, 2016)
Corn is the cultural identity of the Madurese, they being called as maize eaters and included an agrarian society with a kind of shifting agriculture landscape called â€œekologi tegalâ€. Cornfield was once the most important hierarchy in tanÃ¨yan lanjhÃ¨ng. The pattern of rural settlement in Madura is a combination of several clusters tanÃ¨yan lanjhÃ¨ng formed by main moor space hierarchy, then occupancy. Indigenous land use occupancy states should not diminish arable land. But the shift in consumption from maize to rice and Islamic land inheritance system that is uksorilokal and matrilocal changing land use as residential space hierarchy utama.Tujuan this paper is to seek the embodiment and the relationship between the agricultural landscape (dost) with occupancy (tanÃ¨yan lanjhÃ¨ng) so as to form a pattern of settlement , to do with a shift in consumption and a system of inheritance. Discussion method uses anthropologicalarchitectural approach. So characteristic of farming communities in eastern Madura is a problem: the hierarchy of space, the position of women, kinship, social system, as well as the limits of hierarchy, related to settlement patterns. The physical manifestation of settlements tend to the meaning and philosophy of Islam.Keywords: tegal ecology, settlement patterns, tanÃ¨yan lanjhÃ¨ng, meaning and philosophy of Islam